The influence of design and contractor errors on the failure of a tenement building. (March 2019) - Błaszczyński, Tomasz Z.; Sielicki, Piotr W.
Abstract: This paper presents an application of forensic engineering methods in civil engineering problems. Under the case study based on the failure of a tenement building from the 1930s, the authors want to present the analyses of the influence of design and contractor errors on this situation. These analyses were carried out using an advanced computer program - ABAQUS v.6.6. The work was split into three parts. In the first one, only the most cracked wall was analysed as a 2D model. Next, a 3D model of a building fragment with the floor removed was created. In the last stage, the entire building was modelled, including all the structural walls as well as window and door openings. In order to evaluate the percentage responsibility for the building failure, simple FA (failure analysis) was applied. The results show that the most significant influence on the current state resulted from subsequent modernization works and not from the piling works at the site to the north. These simply triggered the accumulated damage in the structure. Highlights: The paper analyses the causes of failure of the building, These analyses were carried out using an advanced computer program - ABAQUS v.6.6, In order to evaluate the percentage responsibility for the building failure, simple FA (failure analysis) was applied, The causes of cracking was analyses and the mechanism was explained, The analysis will be useful for engineers that supervise this kind of building.